Physical mapping of a new powdery mildew resistance locus from Thinopyrum ponticum chromosome 4AgS - Yang, Guotang; Deng, Pingchuan; Ji, Wanquan; Fu, Shulan; Li, Hongwei; Li, Bin; Li, Zhensheng; Zheng, Qi (Frontiers in Plant Science, 2023)
Thinopyrum ponticum (Podp.) Barkworth and D.R. Dewey is a decaploid species that has served as an important genetic resource for improving wheat for the better part of a century. The wheat–Th. ponticum 4Ag (4D) disomic substitution line Blue 58, which was obtained following the distant hybridization between Th. ponticum and common wheat, has been stably resistant to powdery mildew under field conditions for more than 40 years. The transfer of 4Ag into the susceptible wheat cultivar Xiaoyan 81 resulted in powdery mildew resistance, indicating the alien chromosome includes the resistance locus. Irradiated Blue 58 pollen were used for the pollination of the recurrent parent Xiaoyan 81, which led to the development of four stable wheat–Th. ponticum 4Ag translocation lines with diverse alien chromosomal segments. The assessment of powdery mildew resistance showed that translocation line L1 was susceptible, but the other three translocation lines (WTT139, WTT146, and WTT323) were highly resistant. The alignment of 81 specific-locus amplified fragments to the Th. elongatum genome revealed that 4Ag originated from a group 4 chromosome. The corresponding physical positions of every 4Ag-derived fragment were determined according to a cytogenetic analysis, the amplification of specific markers, and a sequence alignment. Considering the results of the evaluation of disease resistance, the Pm locus was mapped to the 3.79–97.12 Mb region of the short arm of chromosome 4Ag. Because of its durability, this newly identified Pm locus from a group 4 chromosome of Th. ponticum may be important for breeding wheat varieties with broad-spectrum disease resistance.